1997
DOI: 10.1074/jbc.272.16.10870
|View full text |Cite
|
Sign up to set email alerts
|

A Translation Regulatory Particle Containing theXenopus Oocyte Y Box Protein mRNP3+4

Abstract: In oocytes, nontranslated maternal mRNAs are packaged by protein into messenger ribonucleoprotein particles (mRNPs) that are masked from translation by protein-RNA interactions. Proteins associated with such masked states of mRNAs are particularly abundant in amphibian oocytes. One of these mRNP proteins from Xenopus oocytes, mRNP3؉4 (also called FRG Y2a/b or p54/p56), binds to diverse mRNAs independent of their sequence and is the germ line member of the evolutionarily conserved Y box protein multigene family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…RlYB2 shared with the Y-box proteins the presence of a highly conserved CSD domain containing two RNP-1 and RNP-2 like motifs that are believed to be important for binding nucleic acids (Sommerville 1999). The presence of numerous residues target for serine/threonine kinases suggested that the RlYB2 activity may be regulated by phosphorylation (Yurkova & Murray 1997). It has been hypothesized that phosphorylation of the C-terminal portion of Ybox proteins facilitates mRNA-protein interactions, while dephosphorylation promotes the release of the bound mRNA (Matsumoto & Wolffe 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RlYB2 shared with the Y-box proteins the presence of a highly conserved CSD domain containing two RNP-1 and RNP-2 like motifs that are believed to be important for binding nucleic acids (Sommerville 1999). The presence of numerous residues target for serine/threonine kinases suggested that the RlYB2 activity may be regulated by phosphorylation (Yurkova & Murray 1997). It has been hypothesized that phosphorylation of the C-terminal portion of Ybox proteins facilitates mRNA-protein interactions, while dephosphorylation promotes the release of the bound mRNA (Matsumoto & Wolffe 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The predicted RlYB2 protein had the highly conserved N-terminal CSD (from aa 37 to 85; Figure 2b) with motifs related to RNP-1 and RNP-2 (Auweter et al 2006). Moreover the sequence contains thirteen putative serine/threonine phosphorylation sites (Yurkova & Murray 1997) and two putative nuclear localization signals (from amino acids 157 to 170; Figure 2b) (Nashchekin et al 2006). An arginine-proline rich profile occurred from aa 114 to 317 (Figure 2b).…”
Section: Isolation and Sequence Analysis Of Rlyb2mentioning
confidence: 99%
“…In addition to being very abundant in the nucleolus, comprising 5 to 10% of the total nucleolar protein, nucleolin was also detected in the cytoplasm (5,8), where its function has only recently been studied (44,45). Like FMRP and the FXR proteins, nucleolin contains an NLS, which enables it to shuttle between the nucleolus and cytoplasm (4,16,26,33).…”
Section: Discussionmentioning
confidence: 99%
“…In the cytoplasm, CSD proteins bind mRNAs, affecting their translation fate (21)(22)(23)(24)(25)(26)(27)(28) and extending their lifetime (29).…”
mentioning
confidence: 99%